Deep Learning Applications - Pier Luigi Mazzeo; Paolo Spagnolo (IntechOpen, 2021)
Deep learning is a branch of machine learning similar to artificial intelligence. The applications of deep learning vary from medical imaging to industrial quality checking, sports, and precision agriculture. This book is divided into two sections. The first section covers deep learning architectures and the second section describes the state of the art of applications based on deep learning.